Synthesis, processing and microstructural characterization of CaSnO3 and SrSnO3 ceramics - Azad, Abdul-Majeed; Shyan, Lucia Liew Woan; Yen, Pang Toh (Elsevier, 1999)
A thorough study of CaSnO3 and SrSnO3 with respect to their synthesis, processing and microstructural characterization has been made. In order to establish a standard methodology for mass manufacturing with identical and beneficial microstructure and reproducible electrical characteristics, different synthesis routes were adopted. Evolution of microstructure which is intimately related to the envisaged properties in the ceramics, was closely and systematically followed in terms of sintering over a wide range of temperatures and soak time. By using an alternative precursor (nitrate instead of carbonate) with favorable decomposition kinetics, the temperature of compound formation by solid-state route was lowered by a significant margin of 200°. In the case of the self-heat-sustained (SHS) method, the final compound was found to have formed via two-step reaction between molten tin and metal nitrate. In CaSnO3, a dense microstructure with near zero porosity and uniform grain size could be developed by sintering at 1200°C up to 48 h, while the solid-state derived SrSnO3 could be sintered to about 85–90% density relative to that of the green compact at 1350°C/24 h. In the case of SHS technique, small grain size and a narrower particle size distribution was an interesting feature of the sintered samples. Sintering at 1350°C for soak-time 48<t≤60 h was found to be the most suitable schedule to obtain dense microstructure in CaSnO3 with average grain size ∼1 μm and, theoretical densification with larger grain size (3–5 μm) could be achieved by sintering at 1600°C for 2 h. The SHS-derived SrSnO3 had very dense (relative density ∼95%) microstructure after sintering at 1350°C for soak-time in the range 12 h<t≤24 h; sintering at higher temperature such as 1600°C even for 2 h was found to be deleterious. Citrate-complex synthesis route yielded very fine, homogeneous and reactive submicron sized CaSnO3 powder, with microstructure benign for making gas sensing devices.